PENGOMPOSAN DENGAN MENGGUNAKAN LUMPUR DARI INSTALASI PENGOLAHAN AIR LIMBAH INDUSTRI KERTAS DAN SAMPAH DOMESTIK ORGANIK - Badrus Zaman; Ika Bagus Priyambada (TEKNIK, 2007)
Waste water treatment of paper industry yield side product in the form of sludge which have generated problembecause there is no continuation processing. Composting sludge which come from waste water processing differfrom other composting organic solid waste, which generally in the form of dry substance. In this research usedadditional substance in the form of organic domestic solid waste, with variation sludge : domestic solid waste(kg/kg) successively 1 : 1, 1 : 4, 1 7, 3 : 2, and 5 : 3. Composting method is done by open windrow, where thecompost heaped longly and let to be opened (aerob). Result of research indicate that to the overall of variationof compost really have fulfilled standard of good ripeness compost according to SNI 19-7030-2003 and alsoaccording to other ripe compost standard. Besides, all variation of compost have yielded ripe compost withcharacteristic fulfilling hara required by crop. Variation Compost 1 : 1 representing the best compost with COrganiccontent 41,507 %, N-Total content 3,008 %, ratio C/N 13,80, moisture rate 44,03 %, P-Total content1,085 %, K-Total content 4,183 %, final temperature 30,3° C and pH 7,98